Considerations in the Choice of the Appropriate Discount Rate for Evaluating Sovereign Debt Restructurings - Kozack, Julie (Washington, D.C. : International Monetary Fund, 2005)
Assessments regarding the effectiveness of sovereign debt restructurings are often summarized by comparisons of the net present value of debt service before and after the restructuring. These calculations are inherently sensitive to the choice of discount rate. This paper explores issues that arise in selecting discount rates when evaluating sovereign debt restructurings. It suggests using a range of discount rates and centering the analysis around the internal rate of return to assess whether the debt restructuring has generated net present value savings or costs to the debtor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet